Technical Analysis of Stock Trends - Edwards, Robert D.; Magee, John; Bassetti, W.H.C.; Taylor and Francis (Boca Raton, FL : Taylor and Francis, an imprint of CRC Press, 2018)
This revised and updated version of the best-selling book, Technical Analysis of Stock Trends, 10th Edition, presents proven long- and short-term stock trend analysis enabling investors to make smart, profitable trading decisions. The book covers technical theory such as The Dow Theory, reversal patterns, consolidation formations, trends and channels, technical analysis of commodity charts, and advances in investment technology. The book also includes a comprehensive guide to trading tactics from long and short goals, stock selection, charting, low and high risk, trend recognition tools, balancing and diversifying the stock portfolio, application of capital, and risk management. This sharpened and updated new edition offers patterns and charts that are tighter and more illustrative, including modifiable charts. Expanded material will be offered on Pragmatic Portfolio Theory as a more elegant alternative to Modern Portfolio Theory; and a newer, simpler, and more powerful alternative to Dow Theory is presented.
Part I: Technical theory -- 1. The technical approach to trading and investing -- 2. Charts -- 3. The Dow Theory -- 4. The Dow Theorys defects -- 5. Replacing Dow Theory with John Magees Basing points Procedure -- 6. Important Reversal Patterns -- 7. Important Reversal Patterns: continued -- 8. Important Reversal Patterns: the Triangles -- 9. More important Reversal Patterns -- 10. Other Reversal phenomena -- 11. Consolidation Formations -- 12. Gaps -- 13. Support and Resistance -- 14. Trendlines and Channels -- 15. Major Trendlines -- 16. Technical analysis of commodity charts -- 17. A summary and concluding comments -- Part II: Trading tactics -- 18. The tactical problem -- 19. The all-important details -- 20. The kind of stocks we want: the speculators viewpoint -- 21. Selection of stocks to chart -- 22. Selection of stocks to chart: continued -- 23. Choosing and managing high-risk stocks: tulip stocks, Internet sector, and speculative frenzies -- 24. The probable moves of your stocks -- 25. Two touchy questions -- 26. Round lots or odd lots? -- 27. Stop orders -- 28. What is a Bottom and what is a Top? -- 29. Trendlines in action -- 30. Use of Support and Resistance -- 31. Not all in one basket -- 32. Measuring implications in technical chart patterns -- 33. Tactical review of chart action -- 34. A quick summation of tactical methods -- 35. Effect of technical trading on market action -- 36. Automated trendline: the Moving Average -- 37. The same old patterns -- 38. Balanced and diversified -- 39. Trial and error -- 40. How much capital to use in trading -- 41. Application of capital in practice -- 42. Portfolio risk management -- 43. Stick to your guns.
Includes bibliographical references and index.
Also available in print format.
Keywords: MATHEMATICS / General; MATHEMATICS / Probability & Statistics / General; Investment analysis; Stock exchanges -- United States; Securities -- United States; Electronic books